Graphene oxide synthesis from coconut fiber powder using triple superphosphate catalyst and its potency for secondary battery electrode - Marcelinus Christwardana; Adhista Fania; Deni Shidqi Khaerudini (Journal of Bioresources and Environmental Sciences, 2024)
Coconut fiber, considered an organic waste, emerges as a promising alternative carbon source for graphene oxide production—a material characterized by its conductive nature due to oxidation and the introduction of functional groups. The synthesis process involves carbonization with varied holding times (10, 20, and 30 minutes) and the utilization of Triple Superphosphate (TSP) and Ferrocene catalysts at concentrations of 10 wt.% and 20 wt.%. Subsequently, the sonication method is employed to enhance the electrical conductivity of graphene oxide post-carbonization. Notably, the electrical conductivity tests, conducted using a sourcemeter, revealed the optimum performance at 20 minutes of carbonization duration and a 20 wt.% TSP catalyst concentration, yielding an impressive electrical conductivity of 11,489.86 S/m. These findings underscore the significance of tailored parameters in optimizing graphene oxide synthesis for applications such as high-conductivity battery anodes.